2015
DOI: 10.1200/jco.2015.61.4503
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hereditary Cancer Syndromes in Adolescents and Young Adults With Colorectal Cancer

Abstract: Purpose Established guidelines recommend evaluation for hereditary cancer syndromes in patients younger than 50 years diagnosed with colorectal cancer (CRC). This group has been well described in the literature; however, patients diagnosed as adolescents and young adults are not well represented in CRC studies. Here, we define the clinical profile, including the extent of hereditary cancer syndromes and family history of cancer, in patients diagnosed with CRC at age 35 or younger. Patients and Methods We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
188
2
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(199 citation statements)
references
References 16 publications
3
188
2
6
Order By: Relevance
“…In the absence of definitive genetic testing, a detailed family history was essential and formed the core of the Amsterdam and Bethesda criteria to make a diagnosis of HNPCC [28,29] . Currently, we know that young patients with an underlying genetic syndrome are more likely to have a family history of cancer and present earlier compared with those with no known genetic syndrome, who presented with late stage metastatic disease [30] . Thus, family history must continue to remain an essential component of clinical evaluation in patients with CRC, while it is essential to note that up to 20 percent of patients with a germline mutation in the study reported by Mork et al [30] had no family history of CRC.…”
Section: Family Historymentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of definitive genetic testing, a detailed family history was essential and formed the core of the Amsterdam and Bethesda criteria to make a diagnosis of HNPCC [28,29] . Currently, we know that young patients with an underlying genetic syndrome are more likely to have a family history of cancer and present earlier compared with those with no known genetic syndrome, who presented with late stage metastatic disease [30] . Thus, family history must continue to remain an essential component of clinical evaluation in patients with CRC, while it is essential to note that up to 20 percent of patients with a germline mutation in the study reported by Mork et al [30] had no family history of CRC.…”
Section: Family Historymentioning
confidence: 99%
“…In young patients, CRC is likely to be found in those with a heritable syndrome [28][29][30] such as FAP and HNPCC.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the traditional paradigm of CRC tends to center around environmental factors such as increased red meat intake and exposure to carcinogens [14], there is evidence of a higher prevalence of genetic risk factors such as Lynch syndrome and familial adenomatous polyposis in YA CRC cases [5]. Additionally, as overall CRC incidence has declined, disparities between racial and ethnic groups have been revealed, as well as variations in race-specific mortality rates [12].…”
mentioning
confidence: 99%
“…There is currently no consensus in the literature regarding the definition of young-onset CRC; however the rising incidence in adolescents and YAs has recently attracted increased attention from physicians, public health officials and investigators [5,12,13]. Although the traditional paradigm of CRC tends to center around environmental factors such as increased red meat intake and exposure to carcinogens [14], there is evidence of a higher prevalence of genetic risk factors such as Lynch syndrome and familial adenomatous polyposis in YA CRC cases [5].…”
mentioning
confidence: 99%